POLTAVA BISCHOFITE SOLUTION APPLICATION FOR ENTEROINFECTIONS PREVENTION AND CALVES COLOSTRUM IMMUNITY FORMATION - Kyrychko, O. B.; Kyrychko, B. P.; Titarenko О. V.; Sydorenko, V. V. (Scientific Progress & Innovations, 2021)
The epizootic situation on the farm with regard to calves’ gastrointestinal tract diseases has been ana-lyzed as well as the preventive measures have been developed. A complex approach including both general sanitary and specific measures to prevent calves enteroinfections has been used. Particular attention has been paid to the timely colostrum feeding with its preliminary quality evaluation, the creation of frozen co-lostrum bank and premises’ disinfection. As a specific prophylaxis, ColiMax-RC complex vaccine has been used for animals’ immunization against Escherichia coli, rotavirus and coronavirus infections. Poltava bis-chofite solution (PBS) has been used to stimulate the immune response when vaccinating cows and transmit-ting colostrum immunity to calves. The preparation was administered orally to the cows of the experimental group in the form of a 4 % solution in distilled water, in the amount of 2 l for 7 days before vaccination and 5 days before revaccination. In the blood of both animal groups, the number of leukocytes and the level of total serum protein increased, but the indicators were higher in the animals treated with PBS. In the blood of cows from the experimental group, as compared with control animals, the number of erythrocytes and hemo-globin significantly increased by 25.7 % (p<0.001) and 15.8 % (p<0.01) respectively. The oxidizing blood properties, the state of cows’ energy metabolism and the level of milk productivity accordingly improved. It has been found that the specific weight of colostrum and immune globulins increased after PBS application. The colostrum specific weight of the experimental group cows counted 1.062±0.004 g/cm, which corre-sponded to excellent quality with a high content of immune globulins and ensured rapid formation of passive immunity. The level of colostrum immune globulins was by 10.6 % higher in comparison with the colostrum of cows from the control group. The scheme of calves enteroinfections’ prevention on the farm allowed to prevent the occurrence of diseases for 100 % of the animals from the experimental group. Calves whose mothers received PBS had a higher body weight and total serum protein as compared with the control group, which shows the level of colostrum immunity transmission.